Happiness sold separately : a novel - Winston, Lolly (New York : Warner Books, 2006)
The marriage of a seemingly perfect couple dissolves into a complicated dance of affairs, lovers, and admirers.
Keywords: Married people -- Fiction; Domestic fiction